A high-hardness, low-density flame-retardant foam for drones and a preparation method thereof

By adopting a foam adhesive synthesis method with specific composition, the needs of medium and high hardness, low density and good flame retardancy of drone equipment are solved, and efficient bonding and safety guarantees are achieved.

CN119410327BActive Publication Date: 2025-04-29SHANGHAI JINQIANG ADHESIVE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510019926.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-29
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing foam glue is difficult to provide high hardness, low density and good flame retardancy in drone equipment, and cannot effectively ensure the safety of drone equipment during operation.

Method used

Component B composed of component A and curing agent composed of polyol polymer, castor oil, gas-phase silica, glycerol, metal catalyst, uniform foaming agent, defoaming agent and specific flame retardant agent are used to synthesize high-hardness, low-density flame retardant foam for drones through multi-stage stirring.

Benefits of technology

The foamed body formed by foam glue is achieved with a hardness of more than 90 and a density of less than 1.3g/mL. It has good flame retardant performance and stability. It can better bond components such as drone equipment heat dissipation modules and ensure the safety of drone equipment during operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of foaming glue, and specifically to a high-hardness, low-density flame-retardant foaming glue for unmanned aerial vehicles and a preparation method thereof; the raw materials for preparing the foaming glue include component A and component B, and the mass ratio of component A to component B is 1: (1-1.2); the component A includes a combination of one or more of a polyol polymer, a vegetable oil, a regulator, a cross-linking agent, a metal catalyst, a uniform foaming agent, water, a defoamer, and a flame retardant; the component B includes a curing agent. The foaming glue provided in the present application can increase the hardness of the foamed body formed by the foaming glue, reduce the density of the foamed body, and improve the flame retardancy of the foamed body, thereby ensuring the safety of the unmanned aerial vehicle equipment in operation; it can improve the uniformity of the size of the pores formed in the foaming glue, improve the phenomenon of fluorescent solution penetration after the foaming glue is foamed, and effectively prevent, for example, liquid leakage problems when agricultural unmanned aerial vehicle equipment is spraying pesticides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foam adhesives, and in particular to a high-hardness, low-density flame-retardant foam adhesive for unmanned aerial vehicles and a preparation method thereof. Background Art

[0002] With the development of science and technology and the improvement of people's living standards, the application and demand of drones in the fields of earthquake prevention and disaster relief, agricultural plant protection, power inspection, etc. are becoming more and more extensive. Therefore, the functions of drone equipment and the performance that needs to be adapted are gradually diversified. The present invention discloses a high-hardness, low-density flame-retardant foam adhesive for drones that can be used to bond parts such as heat dissipation modules of drone equipment. The foam adhesive has good stability, and the foam adhesive can have a certain hardness after foaming, and has the performance requirements of low density and good flame retardancy, which can effectively ensure the safety of drone equipment during operation. With regard to the above requirements, the foam adhesive currently on the market cannot meet market demand.

[0003] The Chinese invention patent with patent publication number CN118388743A discloses a prefabricated polyurethane foam and its preparation method and application. By adopting a chain extender obtained by a special method, the foaming reaction is more complete, so that the polyurethane foam obtained by foaming has good impact absorption and vertical deformation properties; but the good stability of the foam, the certain hardness of the foam after foaming, the low density and good flame retardancy are not disclosed in the patent.

[0004] Therefore, providing a foamed rubber with good stability, and the foamed rubber can have a certain hardness after foaming, and has low density and good flame retardancy is the main technical problem that needs to be solved at present. Summary of the invention

[0005] The first aspect of the present invention provides a high-hardness, low-density flame-retardant foam for drones, wherein the raw materials for preparing the foam include component A and component B, wherein the mass ratio of component A to component B is 1:(1-1.2);

[0006] In parts by weight, the component A includes 400-410 parts of polyol polymer, 60-70 parts of vegetable oil, 15-16 parts of regulator, 10-12 parts of cross-linking agent, 0.8-1.0 parts of metal catalyst, 10-12 parts of foam leveling agent, 0.8-1.0 parts of water, 1-1.2 parts of defoaming agent, and 210-225 parts of flame retardant;

[0007] The B component includes a curing agent;

[0008] The polyol polymer has a hydroxyl value of 300-400 mgKOH / g, and a kinematic viscosity of the polyol polymer at 25° C. of 200-400 mPa·s.

[0009] In a preferred embodiment, the mass ratio of component A to component B is 1:1.

[0010] In one embodiment, the mass ratio of the vegetable oil to the polyol polymer is (60-70):(400-410).

[0011] In one embodiment, the polyol polymer comprises a hydroxyl value of 300-400 mgKOH / g, and a kinematic viscosity of the polyol polymer at 25° C. of 200-400 mPa·s.

[0012] In one embodiment, the polyol polymer has a hydroxyl value of 335±10 mgKOH / g, and a kinematic viscosity of the polyol polymer at 25° C. of 260-380 mPa·s.

[0013] In one embodiment, the polyol polymer includes a combination of one or more of polyether polyol, polyester polyol, and polycarbonate polyol.

[0014] In a preferred embodiment, the polyol polymer is a polyether polyol.

[0015] In one embodiment, the polyether polyol has a hydroxyl value of 335±10 mgKOH / g, a kinematic viscosity of 260-380 mPa·s at 25° C., and the polyether polyol can be purchased from Zibo Dexin Federal Chemical Industry Co., Ltd., model DMN-500.

[0016] In one embodiment, the vegetable oil includes a combination of one or more of castor oil, soybean oil, palm oil, and rapeseed oil.

[0017] In a preferred embodiment, the vegetable oil is castor oil.

[0018] In one embodiment, the castor oil can be purchased from Adani, India.

[0019] In order to increase the hardness of the foamed body formed by the foaming glue to be greater than 90, reduce the density of the foamed body, and effectively ensure the safety of the equipment during the operation of the drone when it is used to bond the heat dissipation module of the drone equipment, the inventor found in the experimental process that when castor oil and a polyether polyol with a hydroxyl value of 335±10mgKOH / g and a viscosity of 200-400mPa·s at 25°C are used for coordination, especially when a polyether polyol with a hydroxyl value of 335±10mgKOH / g and a viscosity of 260-380mPa·s at 25°C and castor oil are used for coordination, when the mass ratio of castor oil to polyether polyol is (60-70): (400-410), the hardness of the foamed body can be increased, the density of the foamed body can be reduced, and the heat dissipation module of the drone equipment and other parts can be better bonded; the possible reason is that castor oil participates in the reaction process of the polyether polyol and the curing agent, and the castor oil improves the thickness of the pore wall and further improves the flexibility of the foamed body; thereby the hardness of the foamed body is increased and the density of the foam is reduced.

[0020] In one embodiment, the specific surface area of ​​the regulator is 100-300m 2 / g.

[0021] In one embodiment, the specific surface area of ​​the regulator is 150-260m 2 / g.

[0022] In one embodiment, the conditioning agent comprises fumed silica.

[0023] In one embodiment, the conditioning agent is fumed silica.

[0024] In one embodiment, the specific surface area of ​​the fumed silica is 175-225 m 2 / g, the manufacturer and model available for purchase is AEROSIL 200 from Evonik Specialty Chemicals (Shanghai) Co., Ltd.

[0025] In order to reduce the density of the foamed body formed by the foam glue and improve the strength of the foamed body formed by the foam glue, so as to better bond the heat dissipation module and other parts of the drone equipment, the inventor found in the experiment that by using a foamed body with a specific surface area of ​​175-225m 2 When the fumed silica of 1000 g is combined with castor oil and polyether polyol with a hydroxyl value of 335 ± 10 mgKOH / g and a kinematic viscosity of 200-400 mPa·s at 25°C, the density of the foam can be reduced and the strength of the foam can be increased. The possible reason is that the specific surface area is 175-225 m 2 / g of fumed silica can adjust the kinematic viscosity of the foam, avoid too many bubbles in series during the foaming process, and affect the uneven distribution of bubbles during the foaming of the foam, thereby reducing the density of the foam and increasing the strength of the foam. It can effectively ensure the safety of the equipment during the operation of the drone when it is used to bond components such as the heat dissipation module of the drone.

[0026] In one embodiment, the cross-linking agent comprises glycerol.

[0027] In one embodiment, the cross-linking agent is glycerol.

[0028] In order to improve the uniformity of the size of the bubbles formed during the foaming process of the foaming glue, the inventors found in the experiment that the use of propylene glycol and a specific surface area of ​​175-225m 2 When propylene glycol is used in combination with castor oil and a polyether polyol having a hydroxyl value of 335±10 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C, the uniformity of the size of the pores formed in the foamed rubber can be improved; the possible reason is that propylene glycol can improve the surface tension of the foamed rubber system and can make the bubbles formed in the foamed rubber system evenly distributed during the foaming process.

[0029] In one embodiment, the metal catalyst includes a combination of one or more of dibutyltin dilaurate, bismuth isooctanoate, stannous isooctanoate, and zinc isooctanoate.

[0030] In one embodiment, the metal catalyst is dibutyltin dilaurate.

[0031] In order to further improve the hardness of the foamed body formed by the foaming glue and reduce the density of the foamed body, the inventors found in the experimental process that when dibutyltin dilaurate is used in the foaming glue system, dibutyltin dilaurate, castor oil, a polyether polyol with a hydroxyl value of 335±10mgKOH / g and a kinematic viscosity of 200-400mPa·s at 25°C, and a curing agent are used in combination, the hardness of the foamed body can be improved and the density of the foamed body can be reduced; the possible reason is that dibutyltin dilaurate can adjust the reaction rate of the polyether polyol and the curing agent, improve the size of the pores in the foamed body and the thickness of the pore walls, thereby improving the hardness of the foamed body and reducing the density of the foamed body.

[0032] The foam leveling agent was purchased from Shanghai Maihao New Material Technology Co., Ltd. and its model is BL-3002.

[0033] The defoaming agent was purchased from Yangzhou Sixin New Materials Technology Co., Ltd. and its model is SX-63.

[0034] In order to avoid the phenomenon of fluorescent solution penetration in the foamed body formed by foaming the foaming glue, the inventors found in the experimental process that by using a foaming agent in combination with polyether polyol and a curing agent, the phenomenon of fluorescent solution penetration in the foamed glue can be improved and the larger pores in the foamed body can be avoided; the possible reason is that the foaming agent can not only improve the structure of the pores, but also reduce the problem of uneven distribution of the pores, thereby further improving the phenomenon of fluorescent solution penetration in the formed foamed body.

[0035] In one embodiment, the flame retardant includes one or a combination of a solid flame retardant and a liquid flame retardant.

[0036] In one embodiment, the flame retardant is a combination of a solid flame retardant and a liquid flame retardant; in parts by weight, the flame retardant includes 150-160 parts of solid flame retardant and 60-65 parts of liquid flame retardant.

[0037] In one embodiment, the liquid flame retardant can be purchased from Doher-6209 of Dongguan Doher New Material Technology Co., Ltd.

[0038] In one embodiment, the solid flame retardant includes a combination of one or more of aluminum hydroxide, magnesium hydroxide, magnesium carbonate, and antimony oxide.

[0039] In one embodiment, the solid flame retardant is aluminum hydroxide.

[0040] In one embodiment, the aluminum hydroxide is purchased from the manufacturer and model OL-104LEO of Huber Group, USA.

[0041] The inventor found in the experiment that in order to improve the colloidal stability of the foam, improve the flame retardancy of the foam, reduce the density of the foam, and better bond the components such as the heat dissipation module of the drone equipment; the inventor found in the experiment that when the aluminum hydroxide of model OL-104 LEO and the liquid flame retardant of model Doher-6209 are used in the present application for cooperation, especially the aluminum hydroxide weight is 150-160 parts, and the liquid flame retardant Doher-6209 is 60-65 parts for cooperation, the obtained foam can be stable and non-stratified within 15 days. And the flame retardant effect of the foam is good, which can reach V0 level, and the density of component A is less than 1.3g / mL, and the density of component A is low, so the density of the foam is low. The possible reason is that the solid flame retardant and the liquid flame retardant affect the kinematic viscosity of the foamed glue during the mixing process of component A and component B, which further affects the density and flame retardant effect of the foam. In this application, specific solid flame retardants and liquid flame retardants are required to improve the colloidal stability of the foamed glue, improve the flame retardancy of the foam, and reduce the density of the foam. This can effectively ensure the safety of the equipment during the operation of the drone when it is used to bond components such as the heat dissipation module of the drone equipment.

[0042] In one embodiment, the curing agent includes an isocyanate.

[0043] In one embodiment, the curing agent includes isocyanate and diphenylmethane diisocyanate.

[0044] In one embodiment, the curing agent is a mixture of isocyanate and diphenylmethane diisocyanate, and the curing agent can be purchased under the manufacturer model WANNATE® PM-200 of Wanhua Chemical Group Co., Ltd.

[0045] The second aspect of the present invention provides a method for preparing a high-hardness, low-density flame-retardant foam for a drone, comprising the following steps:

[0046] S1. The polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foaming agent, water, defoaming agent, and flame retardant are mixed and a component A is obtained by multi-stage stirring;

[0047] S2. Component A and component B are mixed to obtain a high-hardness, low-density flame-retardant foam for drones.

[0048] In one embodiment, the multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage; the stirring speed of the first stirring stage is 600-1000rpm, and the stirring time is 10-30s; the stirring speed of the second stirring stage is 1200-1800rpm, and the stirring time is 20-60s; the stirring speed of the third stirring stage is 1200-1800rpm, and the stirring time is 40-70s.

[0049] In one embodiment, the multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage; the stirring speed of the first stirring stage is 800 rpm, and the stirring time is 20 s; the stirring speed of the second stirring stage is 1600 rpm, and the stirring time is 40 s; the stirring speed of the third stirring stage is 1600 rpm, and the stirring time is 55 s.

[0050] Beneficial Effects

[0051] 1. In the present application, castor oil and polyether polyol having a hydroxyl value of 335±10 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C are used to form a foamed body with a hardness greater than 90 and a reduced density of the foamed body.

[0052] 2. In this application, the specific surface area is 175-225m 2 When fumed silica of 1000 g / g is combined with castor oil and polyether polyol having a hydroxyl value of 335±10 mgKOH / g and a kinematic viscosity of 200-400 mPa·s at 25°C, the density of the foam can be reduced and the strength of the foam can be increased.

[0053] 3. In this application, propylene glycol and a specific surface area of ​​175-225m 2 When fumed silica of 1000 g / g is combined with castor oil and polyether polyol having a hydroxyl value of 335±10 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C, the uniformity of the size of the pores formed in the foaming rubber can be improved.

[0054] 4. In this application, by using dibutyltin dilaurate, castor oil, a polyether polyol with a hydroxyl value of 335±10mgKOH / g and a kinematic viscosity of 200-400mPa·s at 25°C, and a curing agent to cooperate, the hardness of the foam can be increased and the density of the foam can be reduced, and components such as the heat dissipation module of the drone equipment can be better bonded, effectively ensuring the safety of the drone equipment during operation when it is used to bond components such as the heat dissipation module of the drone equipment.

[0055] 5. In the present application, by using a foaming agent in combination with a polyether polyol and a curing agent, the phenomenon of fluorescent solution penetration after the foaming of the foaming glue can be improved, and larger pores in the foam can be avoided.

[0056] 6. In the present application, by using aluminum hydroxide of model OL-104 LEO and liquid flame retardant of model Doher-6209 to cooperate with each other, the colloidal stability of the foamed adhesive can be improved and the flame retardancy of the foam can be improved. DETAILED DESCRIPTION

[0057] Example 1

[0058] In a first aspect, the present embodiment provides a high-hardness, low-density flame-retardant foam for drones, wherein the raw materials for preparing the foam include component A and component B, wherein the mass ratio of component A to component B is 1:1;

[0059] The component A is composed of polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foam leveling agent, water, defoamer and flame retardant;

[0060] The B component is a curing agent.

[0061] In parts by weight, the component A includes 400 parts of a polyol polymer, 60 parts of a vegetable oil, 15 parts of a regulator, 10 parts of a cross-linking agent, 0.8 parts of a metal catalyst, 10 parts of a foaming agent, 0.8 parts of water, 1 part of a defoaming agent, and 210 parts of a flame retardant. The flame retardant is a combination of a solid flame retardant and a liquid flame retardant, wherein the solid flame retardant is 150 parts and the liquid flame retardant is 60 parts.

[0062] The vegetable oil is castor oil.

[0063] The castor oil was purchased from Adani, India.

[0064] The polyol polymer is a polyether polyol.

[0065] The polyether polyol was purchased from Zibo Dexin Federal Chemical Industry Co., Ltd., and the model number was DMN-500.

[0066] The regulator is fumed silica.

[0067] The manufacturer and model of the fumed silica is AEROSIL200 from Evonik Specialty Chemicals (Shanghai) Co., Ltd.

[0068] The cross-linking agent is glycerol.

[0069] The CAS number of the glycerol is 56-81-5.

[0070] The metal catalyst is dibutyltin dilaurate.

[0071] The CAS number of the dibutyltin dilaurate is 77-58-7.

[0072] The foam leveling agent was purchased from Shanghai Maihao New Material Technology Co., Ltd. and its model is BL-3002.

[0073] The defoaming agent was purchased from Yangzhou Sixin New Materials Technology Co., Ltd. and its model is SX-63.

[0074] The flame retardant is a combination of a solid flame retardant and a liquid flame retardant.

[0075] The solid flame retardant is aluminum hydroxide.

[0076] The aluminum hydroxide was purchased from the manufacturer and model OL-104 LEO of Huber Group, USA.

[0077] The liquid flame retardant can be purchased from Doher-6209 of Dongguan Doher New Material Technology Co., Ltd.

[0078] The curing agent is a mixture of isocyanate and diphenylmethane diisocyanate.

[0079] The manufacturer model of the curing agent is WANNATE® PM-200 of Wanhua Chemical Group Co., Ltd.

[0080] A second aspect of the present embodiment provides a method for preparing a high-hardness, low-density flame-retardant foam for a drone, comprising the following steps:

[0081] S1. The polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foaming agent, water, defoaming agent, and flame retardant are mixed and a component A is obtained by multi-stage stirring;

[0082] S2. Component A and component B are mixed to obtain a high-hardness, low-density flame-retardant foam for drones.

[0083] The multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage; the stirring speed of the first stirring stage is 800 rpm, and the stirring time is 20 s; the stirring speed of the second stirring stage is 1600 rpm, and the stirring time is 40 s; the stirring speed of the third stirring stage is 1600 rpm, and the stirring time is 55 s.

[0084] Example 2

[0085] In a first aspect, this embodiment provides a high-hardness, low-density flame-retardant foam for drones. The specific implementation is the same as that of Example 1, except that the mass ratio of component A to component B is 1:1.2.

[0086] The component A is composed of polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foam leveling agent, water, defoamer and flame retardant;

[0087] The B component is a curing agent.

[0088] In parts by weight, the component A includes 400 parts of a polyol polymer, 60 parts of a vegetable oil, 15 parts of a regulator, 10 parts of a cross-linking agent, 0.8 parts of a metal catalyst, 10 parts of a foaming agent, 0.8 parts of water, 1 part of a defoaming agent, and 210 parts of a flame retardant. The flame retardant is a combination of a solid flame retardant and a liquid flame retardant, wherein the solid flame retardant is 150 parts and the liquid flame retardant is 60 parts.

[0089] The vegetable oil is castor oil.

[0090] The polyol polymer is a polyether polyol.

[0091] The regulator is fumed silica.

[0092] The cross-linking agent is glycerol.

[0093] The CAS number of the glycerol is 56-81-5.

[0094] The metal catalyst is dibutyltin dilaurate.

[0095] The CAS number of the dibutyltin dilaurate is 77-58-7.

[0096] The flame retardant is a combination of a solid flame retardant and a liquid flame retardant.

[0097] The solid flame retardant is aluminum hydroxide.

[0098] The curing agent is a mixture of isocyanate and diphenylmethane diisocyanate.

[0099] The castor oil, polyether polyol, fumed silica, foam leveler, defoamer, aluminum hydroxide, liquid flame retardant, and curing agent were purchased from the same manufacturers and models as in Example 1.

[0100] A second aspect of the present embodiment provides a method for preparing a high-hardness, low-density flame-retardant foam for a drone, comprising the following steps:

[0101] S1. The polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foaming agent, water, defoaming agent, and flame retardant are mixed and a component A is obtained by multi-stage stirring;

[0102] S2. Component A and component B are mixed to obtain a high-hardness, low-density flame-retardant foam for drones.

[0103] The multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage; the stirring speed of the first stirring stage is 800 rpm, and the stirring time is 20 s; the stirring speed of the second stirring stage is 1600 rpm, and the stirring time is 40 s; the stirring speed of the third stirring stage is 1600 rpm, and the stirring time is 55 s.

[0104] Example 3

[0105] In a first aspect, the present embodiment provides a high-hardness, low-density flame-retardant foam for drones, wherein the raw materials for preparing the foam include component A and component B, wherein the mass ratio of component A to component B is 1:1;

[0106] The component A is composed of polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foam leveling agent, water, defoamer and flame retardant;

[0107] The B component is a curing agent.

[0108] In parts by weight, the component A includes 410 parts of a polyol polymer, 70 parts of a vegetable oil, 16 parts of a regulator, 12 parts of a cross-linking agent, 1.0 parts of a metal catalyst, 12 parts of a foaming agent, 1.0 parts of water, 1.2 parts of a defoaming agent, and 225 parts of a flame retardant. The flame retardant is a combination of a solid flame retardant and a liquid flame retardant, wherein the solid flame retardant accounts for 160 parts and the liquid flame retardant accounts for 65 parts.

[0109] The vegetable oil is castor oil.

[0110] The polyol polymer is a polyether polyol.

[0111] The regulator is fumed silica.

[0112] The cross-linking agent is glycerol.

[0113] The CAS number of the glycerol is 56-81-5.

[0114] The metal catalyst is dibutyltin dilaurate.

[0115] The CAS number of the dibutyltin dilaurate is 77-58-7.

[0116] The flame retardant is a combination of a solid flame retardant and a liquid flame retardant.

[0117] The solid flame retardant is aluminum hydroxide.

[0118] The curing agent is a mixture of isocyanate and diphenylmethane diisocyanate.

[0119] The castor oil, polyether polyol, fumed silica, foam leveler, defoamer, aluminum hydroxide, liquid flame retardant, and curing agent were purchased from the same manufacturers and models as in Example 1.

[0120] A second aspect of the present embodiment provides a method for preparing a high-hardness, low-density flame-retardant foam for a drone, comprising the following steps:

[0121] S1. The polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foaming agent, water, defoaming agent, and flame retardant are mixed and a component A is obtained by multi-stage stirring;

[0122] S2. Component A and component B are mixed to obtain a high-hardness, low-density flame-retardant foam for drones.

[0123] The multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage; the stirring speed of the first stirring stage is 800 rpm, and the stirring time is 20 s; the stirring speed of the second stirring stage is 1600 rpm, and the stirring time is 40 s; the stirring speed of the third stirring stage is 1600 rpm, and the stirring time is 55 s.

[0124] Comparative Example 1

[0125] Comparative Example 1 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the aluminum hydroxide used in component A in Comparative Example 1 is purchased from H-WF-08 of Xinxiang Shengda Aluminum Hydroxide Co., Ltd.

[0126] Comparative Example 2

[0127] Comparative Example 2 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the aluminum hydroxide used in component A in Comparative Example 2 is purchased from H-WF-10 of Xinxiang Shengda Aluminum Hydroxide Co., Ltd.

[0128] Comparative Example 3

[0129] Comparative Example 3 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the liquid flame retardant used in component A in Comparative Example 3 is purchased from diethyl ethylphosphonate (DEEP flame retardant) of Shandong Mobai Chemical Co., Ltd.

[0130] Comparative Example 4

[0131] Comparative Example 4 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the liquid flame retardant used in component A in Comparative Example 4 is purchased from WB-1 of Xinxiang Jinsheng New Materials Co., Ltd.

[0132] Comparative Example 5

[0133] Comparative Example 5 provides a foaming adhesive, and the specific implementation method is the same as that of Example 1, except that component A in Comparative Example 5 does not use a liquid flame retardant.

[0134] Comparative Example 6

[0135] Comparative Example 6 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that component A in Comparative Example 6 does not use solid flame retardant aluminum hydroxide.

[0136] Comparative Example 7

[0137] Comparative Example 7 provides a foaming glue, and the specific implementation method is the same as Example 1, except that component A in Comparative Example 7 uses 360 parts of flame retardant, and the flame retardant is a combination of a solid flame retardant and a liquid flame retardant, wherein the solid flame retardant is 300 parts and the liquid flame retardant is 60 parts.

[0138] Comparative Example 8

[0139] Comparative Example 8 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 8 is purchased from Zibo Dexin Federal Chemical Industry Co., Ltd., and the model is DMN-3050D.

[0140] Comparative Example 9

[0141] Comparative Example 9 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 9 is purchased from DL-400 of Sinochem Dongda (Zibo) Co., Ltd.

[0142] Comparative Example 10

[0143] Comparative Example 10 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 10 is purchased from MN-700 of Sinochem Dongda (Zibo) Co., Ltd.

[0144] Comparative Example 11

[0145] Comparative Example 11 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 11 is purchased from MN-1000 of Sinochem Dongda (Zibo) Co., Ltd.

[0146] Comparative Example 12

[0147] Comparative Example 12 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that component A in Comparative Example 12 does not use castor oil.

[0148] Comparative Example 13

[0149] Comparative Example 13 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 13 is 300 parts by weight.

[0150] Comparative Example 14

[0151] Comparative Example 14 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that the polyether polyol used in component A in Comparative Example 14 is 500 parts by weight.

[0152] Comparative Example 15

[0153] Comparative Example 15 provides a foaming glue, and the specific implementation method is the same as that of Example 1, except that no foaming agent is used in component A in Comparative Example 15.

[0154] Performance Testing

[0155] 1. Density test of component A:

[0156] Test method: Component A of Examples 1-3 and Comparative Examples 1-15 was placed in a 50 mL density cup. The cup was gently tapped while the liquid was added to remove bubbles. The mass of the loaded component A was weighed, and the density of the component A was obtained according to the density formula ρ=m / v. The density of the foam was positively correlated with the density of the component A. The test results are shown in Table 1.

[0157] 2. Determination of hardness:

[0158] Test method: After mixing the components A and B provided in Examples 1-3 and Comparative Examples 1-15 evenly, wait for 30 minutes for the foaming of the foaming glue to complete to obtain a foam body, and measure the hardness of the foam body with a Shore A hardness tester. The average value of the results obtained three times is calculated, which is the hardness value of the foam body. The test results are shown in Table 1.

[0159] 3. Flame retardancy (UL94-V0) test:

[0160] Test method: The components A and B provided in Examples 1-3 and Comparative Examples 1-15 were mixed evenly and injected into a mold. After molding at 25°C for 3 hours, they were cut into 6 mm thick test strips. According to the test standard "GB / T 2408-2008 Horizontal and vertical methods for determination of combustion performance of plastics", the test samples of the embodiments and comparative examples were subjected to two consecutive 10-second combustion tests, and the time for the samples to go out after leaving the flame and the presence or absence of dripping of burning materials were recorded to further determine the flame retardant grade of the samples. The test results are shown in Table 1.

[0161] 4. Respiratory effect test:

[0162] Test method: After mixing components A and B in the embodiment and the comparative example evenly, wait for the foaming glue to be completely foamed, and after curing at 25°C for 2 hours, wrap the foam sample with a dust-free cloth soaked in fluorescent water and put it into a ziplock bag, and place it in a constant temperature and humidity chamber for high and low temperature (-15~80°C) cycle for 200 hours, wherein the temperature is kept constant for 30 minutes when it reaches the lowest and highest points respectively, and observe whether the foam has cracking, bubbling, stratification, and whether the fluorescent solution penetrates into the foam. The test results are shown in Table 1.

[0163] 5. Stability test:

[0164] Test method: visual inspection, observe whether the component A provided in the embodiment and the comparative example is placed in a container for 15 days to see whether the colloid has liquid and solid stratification. The test results are shown in Table 1.

[0165] Table 1

[0166]

[0167] It can be seen from the test results in Table 1 that the component raw materials of different foaming glues provided in the embodiments and comparative examples of the present application, the use of raw materials in component A and component B, especially the type selection of castor oil and polyol polymer, the type selection of flame retardant, the type selection of cross-linking agent, metal catalyst, type selection of foaming agent, all affect the colloidal stability of the foaming glue, the flame retardancy of the foaming glue forming the foam body and the density of the foam body, and also cause the foam body to have problems such as fluorescent solution penetration. The use of the raw materials in component A and component B defined in the present application can increase the hardness of the foaming glue forming the foam body to be greater than 90, reduce the density of the foam body, increase the strength of the foaming glue forming the foam body, improve the uniformity of the size of the pores formed in the foaming process of the foaming glue, avoid the phenomenon of fluorescent solution penetration in the foaming glue formed after the foaming glue is foamed, and improve the flame retardant performance, which can better bond the components such as the heat dissipation module of the unmanned aerial vehicle equipment, effectively guarantee the safety of the equipment of the unmanned aerial vehicle during operation when it is applied to the bonding of the heat dissipation module of the unmanned aerial vehicle equipment.

Claims

1. A high-hardness, low-density flame-retardant foam for drones, characterized in that: The raw materials for preparation thereof include component A and component B, wherein the mass ratio of component A to component B is 1:(1-1.2); In parts by weight, the component A includes 400-410 parts of polyol polymer, 60-70 parts of vegetable oil, 15-16 parts of regulator, 10-12 parts of cross-linking agent, 0.8-1.0 parts of metal catalyst, 10-12 parts of foam leveling agent, 0.8-1.0 parts of water, 1-1.2 parts of defoaming agent, and 210-225 parts of flame retardant; The B component includes a curing agent; The polyol polymer comprises a hydroxyl value of 300-400 mgKOH / g, and a kinematic viscosity of the polyol polymer at 25° C. of 200-400 mPa·s; The polyol polymer is a polyether polyol; The vegetable oil is castor oil; In parts by weight, the flame retardant includes 150-160 parts of solid flame retardant and 60-65 parts of liquid flame retardant; The solid flame retardant is aluminum hydroxide; The model of the aluminum hydroxide is OL-104 LEO; The model of the liquid flame retardant is Doher-6209.

2. The high-hardness, low-density flame-retardant foam for drones as claimed in claim 1, characterized in that: The specific surface area of ​​the regulator is 100-300m 2 / g.

3. The high-hardness, low-density flame-retardant foam for drones as claimed in claim 1, characterized in that: The metal catalyst includes one or more of dibutyltin dilaurate, bismuth isooctanoate, stannous isooctanoate and zinc isooctanoate.

4. The high-hardness, low-density flame-retardant foam for drones as claimed in claim 1, characterized in that: The curing agent includes isocyanate.

5. A method for preparing the high-hardness, low-density flame-retardant foam for drones as claimed in claim 1, characterized in that: The following steps are involved: S1. The polyol polymer, vegetable oil, regulator, cross-linking agent, metal catalyst, foaming agent, water, defoaming agent, and flame retardant are mixed and a component A is obtained by multi-stage stirring; S2. Component A and component B are mixed to obtain a high-hardness, low-density flame-retardant foam for drones.

6. The method for preparing the high-hardness, low-density flame-retardant foamed adhesive for drones as claimed in claim 5, characterized in that: The multi-stage stirring method in S1 includes a first stirring stage, a second stirring stage, and a third stirring stage.

7. The method for preparing the high-hardness, low-density flame-retardant foamed adhesive for drones according to claim 6, characterized in that: The stirring speed of the first stirring stage is 600-1000rpm, and the stirring time is 10-30s; the stirring speed of the second stirring stage is 1200-1800rpm, and the stirring time is 20-60s; the stirring speed of the third stirring stage is 1200-1800rpm, and the stirring time is 40-70s.

Citation Information

Patent Citations

  • Prefabricated polyurethane foam as well as preparation method and application thereof

    CN118388743A

  • Polyurethane polystyrene foam as well as preparation method and application thereof

    CN119161841A